1999
DOI: 10.1159/000027428
|View full text |Cite
|
Sign up to set email alerts
|

A Major Review of Antimetabolites in Glaucoma Therapy

Abstract: Antimetabolites have been used in combination with filtering surgery to improve surgical results for more than 10 years. Based on research published since the introduction of antimetabolites right up to date, we discuss the various forms of antimetabolites that have been used, including drugs and irradiation. Among the drugs used, mitomycin C and 5-fluorouracil are the most prominent. We discuss the background of these agents, the progress in the use of antimetabolites and the research done on these drugs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 54 publications
0
28
0
1
Order By: Relevance
“…It has been also shown that 5-FU inhibits fibroblast proliferation in tissue cultures [27] . As a result, this drug has been widely used in the treatment of some non-malignant diseases, such as hypertrophic scars, actinic keratosis, trabeculectomy and glaucoma surgery [28,29] . However, fibroblastic cell reaction or 5-FU's fibrotic effects may differ due to its different applications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also shown that 5-FU inhibits fibroblast proliferation in tissue cultures [27] . As a result, this drug has been widely used in the treatment of some non-malignant diseases, such as hypertrophic scars, actinic keratosis, trabeculectomy and glaucoma surgery [28,29] . However, fibroblastic cell reaction or 5-FU's fibrotic effects may differ due to its different applications.…”
Section: Discussionmentioning
confidence: 99%
“…Use of antimetabolites during surgeries could effectively modulate this process; however, it can also cause particular problems and severe side-effects, such as leakage, infection, hypotony, and endophthalmitis [1,2]. Therefore, antifibrotic agents that can modulate wound healing more safely and effectively are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been investigated in order to avoid naturally occurring scarring of the filtering bleb and subsequent to lower the incidence of this detrimental complication. Antimetabolic drugs, 5-fluorouracil (5-FU) or mitomycin C (MMC), are the two most widely used cytotoxic agents for intraoperative or postoperative application 1,2. Despite the positive effect MMC has on filtering surgery success rates, its diffusion into adjacent ocular tissues may lead to toxic effects on cells not targeted during treatment 3–5…”
Section: Introductionmentioning
confidence: 99%